2013
DOI: 10.1088/0960-1317/23/9/095016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of monodisperse PEG hydrogel composite microspheres via microfluidic chip with rounded channels

Abstract: An effective microfluidic method to fabricate monodisperse polyethylene glycol (PEG) hydrogel composite microspheres with tunable dimensions and properties is reported in this paper. A T-junction microfluidic chip equipped with rounded channels and online photopolymerization system is applied for the microsphere microfabrication. The shape and size of the microspheres are well controlled by the rounded channels and PEG prepolymer/silicon oil flow rate ratios. The obtained PEG/aspirin composite microspheres exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The tendency of the MPs´ diameters regarding Qc is that the diameter of the MPs is inversely proportional to the increase in the flow of Qc; this is represented in Equation (3), and these results are consistent with those of other authors [ 33 , 34 , 35 , 42 , 43 , 49 ]. However, with this study, we can observe that Qc is the most important factor in relation to the diameter of MPs .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The tendency of the MPs´ diameters regarding Qc is that the diameter of the MPs is inversely proportional to the increase in the flow of Qc; this is represented in Equation (3), and these results are consistent with those of other authors [ 33 , 34 , 35 , 42 , 43 , 49 ]. However, with this study, we can observe that Qc is the most important factor in relation to the diameter of MPs .…”
Section: Resultssupporting
confidence: 91%
“…In Table 1 , it can be observed that none of these studies have used eosine Y as a photo-initiator to start the curing process [ 38 , 40 , 41 , 42 , 43 , 44 ]. In this work, eosin Y is used as the photo-initiator, which needs light with a wavelength of about 520 nm, or visible light [ 2 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that microfluidic is effective way for accurate control of synthetic titania colloidal particles. Droplet microfluidics is also used to synthesize polymer particles by means of polymerization with an online ultraviolet (UV) curing lamp . Additionally, polymer colloidal particles (e.g., polystyrene, polymethyl methacrylate) can also be obtained from droplet microfluidic chips with optimized conditions.…”
Section: Microfluidic Classification and Synthesis Of Colloidal Partimentioning
confidence: 99%
“…There have been several methods reported for producing microparticles. For instance, the monodispersed microfluidic approach is commonly used to create collagen microspheres [24][25][26][27][28][29][30]. The high throughput production is the main advantage of this approach; however, it has not been successful in biomedical applications because oil phase contamination inhibits cellular function in collagen microparticles.…”
Section: Introductionmentioning
confidence: 99%